Large Volume Electron Microscopy and Neural Microcircuit Analysis - Kubota, Yoshiyuki; Sohn, Jaerin; Kawaguchi, Yasuo (Frontiers in Neural Circuits, 2018)
One recent technical innovation in neuroscience is microcircuit analysis using three-dimensional reconstructions of neural elements with a large volume electron microscopy data set. Large-scale data sets are acquired with newly-developed electron microscope systems such as automated tape-collecting ultramicrotomy (ATUM) with scanning electron microscopy (SEM), serial block-face electron microscopy (SBEM), and focused ion beam-scanning electron microscopy (FIB-SEM). Currently, projects are also underway to develop computer applications for the registration and segmentation of the serially-captured electron micrographs that are suitable for analyzing large volume EM data sets thoroughly and efficiently. The analysis of large volume data sets can bring innovative research results. These recently available techniques promote our understanding of the functional architecture of the brain.